2023
DOI: 10.1002/sd.2781
|View full text |Cite
|
Sign up to set email alerts
|

Roadmap to achieving sustainable development: Does digital economy matter in industrial green transformation?

Xiaodong Yang,
Yang Xu,
Asif Razzaq
et al.

Abstract: The rapid advancements in the digital economy have created numerous opportunities and solutions for industrial green transformation. However, the complex relationship between these two has received relatively less attention. Therefore, this study analyses how the digital economy impacts industrial green transformation across 30 Chinese provinces. The empirical findings highlight the digital economy's significant role in driving industrial green transformation. Within this dynamic framework, two crucial operati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(3 citation statements)
references
References 105 publications
1
2
0
Order By: Relevance
“…We found that while the digital economy initially has a positive impact on mining, it may shift to an inverted U-shaped curve over time, in contrast to the manufacturing sector where significant effects become apparent only after reaching a certain threshold of investment. Additionally, consistent with the literature [56], we identify industrial structure upgrading as crucial for efficiency and low-carbon development. We also observed spatial spillover effects of the digital economy, aligning with the findings of the literature [57,58], which highlight its extensive impact across different industries and regions.…”
Section: Analysis Of Spatial Effectssupporting
confidence: 86%
“…We found that while the digital economy initially has a positive impact on mining, it may shift to an inverted U-shaped curve over time, in contrast to the manufacturing sector where significant effects become apparent only after reaching a certain threshold of investment. Additionally, consistent with the literature [56], we identify industrial structure upgrading as crucial for efficiency and low-carbon development. We also observed spatial spillover effects of the digital economy, aligning with the findings of the literature [57,58], which highlight its extensive impact across different industries and regions.…”
Section: Analysis Of Spatial Effectssupporting
confidence: 86%
“…On the other hand, there is huge potential and scope for companies to reap economic benefits through energy saving and emission reduction [49,50]. In comparison, after acquiring resources through green M&As to build a good foundation, heavy polluters are more willing to choose a strategy that meets environmental regulation standards [36], change their previous crude development model and take the initiative to implement a green technology leadership strategy to deepen their innovation research to enhance their core competitiveness, corporate value and industry status [51,52]. Therefore, we believe that the implementation of green M&A by heavily polluting companies can drive their environmental performance through green technology innovation.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Although green innovation is regarded as a source of living water for optimizing industrial structure, the impact of agglomeration externalities on it has rarely been studied [ 19 ]. The literature related to productive services has focused on manufacturing convergence, GDP and energy efficiency [ [20] , [21] , [22] , [23] ]. Some learners have also explored the impact of PSAE on regional innovation.…”
Section: Introductionmentioning
confidence: 99%